Identifying biomarker-driven subphenotypes of cardiogenic shock: analysis of prospective cohorts and randomized controlled trialsResearch in context - Sabri Soussi; Tuukka Tarvasmäki; Antoine Kimmoun; Mojtaba Ahmadiankalati; Feriel Azibani; Claudia C. dos Santos; Kevin Duarte; Etienne Gayat; Jacob C. Jentzer; Veli-Pekka Harjola; Benjamin Hibbert; Christian Jung; et al. (EClinicalMedicine)
Summary: Background: Cardiogenic shock (CS) is a heterogeneous clinical syndrome, making it challenging to predict patient trajectory and response to treatment. This study aims to identify biological/molecular CS subphenotypes, evaluate their association with outcome, and explore their impact on heterogeneity of treatment effect (ShockCO-OP, NCT06376318). Methods: We used unsupervised clustering to integrate plasma biomarker data from two prospective cohorts of CS patients: CardShock (N = 205 [2010–2012, NCT01374867]) and the French and European Outcome reGistry in Intensive Care Units (FROG-ICU) (N = 228 [2011–2013, NCT01367093]) to determine the optimal number of classes. Thereafter, a simplified classifier (Euclidean distances) was used to assign the identified CS subphenotypes in three completed randomized controlled trials (RCTs) (OptimaCC, N = 57 [2011–2016, NCT01367743]; DOREMI, N = 192 [2017–2020, NCT03207165]; and CULPRIT-SHOCK, N = 434 [2013–2017, NCT01927549]) and explore heterogeneity of treatment effect with respect to 28-day mortality (primary outcome). Findings: Four biomarker-driven CS subphenotypes (‘adaptive’, ‘non-inflammatory’, ‘cardiopathic’, and ‘inflammatory’) were identified separately in the two cohorts. Patients in the inflammatory and cardiopathic subphenotypes had the highest 28-day mortality (p (log-rank test) = 0.0099 and 0.0055 in the CardShock and FROG-ICU cohorts, respectively). Subphenotype membership significantly improved risk stratification when added to traditional risk factors including the Society for Cardiovascular Angiography and Interventions (SCAI) shock stages (increase in Harrell's C-index by 4% (p = 0.033) and 6% (p = 0.0068) respectively in the CardShock and the FROG-ICU cohorts). The simplified classifier identified CS subphenotypes with similar biological/molecular and outcome characteristics in the three independent RCTs. No significant interaction was observed between treatment effect and subphenotypes. Interpretation: Subphenotypes with the highest concentration of biomarkers of endothelial dysfunction and inflammation (inflammatory) or myocardial injury/fibrosis (cardiopathic) were associated with mortality independently from the SCAI shock stages. Funding: Dr Sabri Soussi was awarded the Canadian Institutes of Health Research (CIHR) Doctoral Foreign Study Award (DFSA) and the Merit Awards Program (Department of Anesthesiology and Pain Medicine, University of Toronto, Canada) for the current study.